POSTCOLONIAL READING OF WOLE SOYINKA’S THE LION AND THE JEWEL AND JEAN PLIYA’S LA SECRÉTAIRE PARTICULIÈRE - Ogundokun, Sikiru (Al-Adab Journal, 2024)
In literary criticism, both the context and the content of a given text; speech, graph, image, or picture are essential. It is the totality of these two elements that pave the way for a better understanding of any given text. Hence, since the purpose of every communication or speech act is comprehension, this study examines the stylistic profile of Wole Soyinka and Jean Pliya in The Lion and the Jewel (1964) and La secrétaire particulière (2001) respectively. The study adopts the French ‘explication de texte’ technique as its methodology to carry out a textual analysis of the two selected plays. As a theoretical framework, the study uses Edward Said and Homi Bhabha’s Postcolonial theory which interrogates the effects of the interactions between the centre and the margin with the view to reconstructing the worldview on matters of history, race, identity, and culture. Findings reveal that in resisting colonial domination and imposition, the two African playwrights take advantage of linguistic manipulations in the composition of their literary texts. With the application of transliteration, direct translation, proverbs, figures of speech, allusions, lexical borrowing, and grammatical and phonemic corruption, the writers are able to foreground their intention to post-colonialize and africanize their literary works.